Photocatalytic MOC materials: Engineering strategies, limitations, and future outlook - Edith Luévano-Hipólito; Leticia M. Torres-Martínez (Next Materials, 2025)
The implementation of heterogeneous photocatalysis in building materials has emerged as a promising technology to tackle environmental pollutants. In this context, photocatalytic magnesium oxychloride cement (MOC) represents a sustainable building material capable of reducing air pollution, maintaining cleaner surfaces by removing environmental agents, and inhibiting the growth of pathogenic microorganisms. Beyond these environmental benefits, MOC offers intrinsic advantages over conventional cementitious materials, such as a lower carbon footprint, rapid setting time, and excellent fire resistance. However, its photocatalytic activity remains underexplored. This review critically examines the development of photocatalytic MOC materials, focusing on fabrication methods, functional additives, and their synergy with photocatalytic activity for environmental depollution. Although various photocatalysts such as TiO2, g-C3N4, and Ag-based nanoparticles, have been successfully incorporated into MOC, significant challenges remain, including water sensitivity, long-term durability under realistic conditions, and UV exposure. This review outlines these limitations, identifies key knowledge gaps, and proposes future research directions to advance the practical implementation of photocatalytic MOC in sustainable construction and urban air purification.